A review of the lycophyte and fern names treated as new in Carl Peter Thunberg’s Flora Japonica - Mazumdar, Jaideep; Ebihara, Atsushi (Phytotaxa, 2019)
Following the advice of Carl Linnaean, his apostle Carl Peter Thunberg first explored Japan, a forbidden country for Europeans at that time. Thunberg collected several plants from Japan and described them in detail in his Flora Japonica. He also introduced some new species, the names of which are still accepted today, but as he published them later than their first publication he did not validly publish them. Here a revised list is presented of these lycophyte and fern (pteridophyte) names considered by Thunberg to be new, along with their valid publication details, type information and currently accepted names.